2008
DOI: 10.1017/s0025315408001197
|View full text |Cite
|
Sign up to set email alerts
|

Response of benthic foraminifera Rosalina leei to different temperature and salinity, under laboratory culture experiment

Abstract: Live specimens of benthic foraminiferal species Rosalina leei were subjected to a combination of temperature (25°C, 30°C and 35°C) and salinity (25‰, 30‰ and 35‰) to assess its differential response to the annual range of seawater temperature and salinity reported at the sampling site. A total of 216 specimens were used for the experiment. Within the range of temperature and salinity, to which R. leei specimens were subjected as part of the present experiment, growth increased with increasing salinity, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…Our findings are also supported by Boltovskoy et al (1991) who summarized that decrease in temperature leads to smaller shells of the same species. This study also contradicts the findings of Nigam et al (2008) who noted that the specimens of Rosalina leei subjected to 25°C temperature showed more growth compared to the specimens subjected to 30°C and 35°C temperatures. This indicates that the species belonging to the same genus may have different temperature preferences.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our findings are also supported by Boltovskoy et al (1991) who summarized that decrease in temperature leads to smaller shells of the same species. This study also contradicts the findings of Nigam et al (2008) who noted that the specimens of Rosalina leei subjected to 25°C temperature showed more growth compared to the specimens subjected to 30°C and 35°C temperatures. This indicates that the species belonging to the same genus may have different temperature preferences.…”
Section: Discussioncontrasting
confidence: 99%
“…Previously, it was observed that outside the reproductive temperature limits, the foraminifera remain alive and yet not reproduce and also that though foraminifera reach maturity, they reproduce only if the environmental conditions are favorable (Bradshaw 1955(Bradshaw , 1957. Nigam et al (2008) also noticed that, specimens of Rosalina leei did not reproduce at any of the temperatures to which they were subjected to in the laboratory (25ºC, 30ºC and 35ºC), but the specimens survived for longer time, as well as showed significant growth at all the three temperatures. They also suggested that none of the temperatures at which Rosalina leei was maintained in laboratory, was favorable for its reproduction.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, there is limited evidence of the effects of ocean warming and acidification in these two important carbonate sediment producers. Elevated seawater temperatures of 30uC to 35uC reduced the growth rate in the benthic foraminifera Rosalina leei Hedley and Wakefield (Nigam et al 2008) and induced algal symbiont loss in Amphistegina gibbosa d'Orbigny when temperatures reached 32uC (Talge and Hallock 2003). Borowitzka and Larkum (1976) showed an inhibition in calcification in Halimeda tuna (Ellis and Solander) Lamouroux when seawater pH was dropped from 8.0 to 7.5.…”
mentioning
confidence: 99%